Military construction and military duty in Dagestan in 1928–1940: a historical and socio-cultural aspects - G. Sh. Kaymarazov; L. G. Kaymarazova (Вестник Майкопского государственного технологического университета, 2024)
The article considers the historical and socio-cultural aspects of military development in the Dagestan Autonomous Soviet Socialist Republic from 1928 to 1940, taking into account the growing interest in society and the scientific community in military history, including the problem of involving the peoples of national regions of the country in the process of formation and further development of the Soviet Armed Forces. In the research the principles of historicism, scientific objectivity, as well as comparative historical, problem-chronological, statistical and descriptive methods have been used; new publications and documentary sources that have not previously been introduced into scientific circulation have been employed.The historical and social and cultural aspects of military development in the Dagestan Autonomous Soviet Socialist Republic from 1928 to 1940 have been considered. - from the moment of the first compulsory conscription of Dagestanis for military service in the ranks of the Workers 'and Peasants' Red Army (RKKA) until the adoption in September 1939 by the Supreme Soviet of the USSR of the new Law “On General Military Duty”. This event marked the beginning of the implementation of military service by representatives of the male youth of the peoples of Dagestan service on a common basis with all nationalities of the USSR.The research characterizes the work of the authorities to establish military registration of the male part of the population and pre-conscription training of young people in a multinational region. The gender component of the process of formation of military service has been highlighted; the features of the implementation of Soviet military construction in Dagestan within the designated chronological framework identified and prospects and scope of application of the research results characterized.